Distance Magic Labeling of Corona Product of Graphs - Nadeak, Christyan Tamaro (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2024)
Let G = (V, E) is a graph with order n, and f: V(G) → {1,2,...,n} is a bijection. For any vertex v ϵ V, the sum of f(u) is called the weight of vertex v, denoted by w(v), where N(v)  is the set of neighbors of vertex v. If the labeling f satisfies that there exists a constant k such that w(v)=k, for every vertex v in the graph G, then f is called a distance magic labeling for the graph G. If a graph G has a distance magic labeling, then G is called a distance magic graph. This paper presents a novel result that has not been extensively explored in previous research on the distance magic labeling for the corona product between several families of graphs, such as a complete, cycle, path, and star graph.Keywords: distance magic labeling; corona product; complete graph; cycle graph; path graph; star graph. AbstrakMisalkan G = (V, E) adalah graf berorde n, dan f: V(G) → {1,2,...,n}  merupakan suatu bijeksi. Untuk sebarang titik vϵ V, jumlahan dari f(u) merupakan bobot dari titik v dan dinotasikan dengan w(v), dengan N(v) merupakan himpunan tetangga dari titik v. Jika pelabelan f memenuhi terdapat suatu konstanta k sehingga w(v)=k, untuk setiap titik v yang terdapat pada graf G, maka f disebut sebagai pelabelan ajaib jarak bagi graf G. Jika suatu graf G memiliki pelabelan ajaib jarak, maka G disebut sebagai graf ajaib jarak. Paper ini memberikan hasil yang belum pernah dibahas sebelumnya, yaitu pelabelan ajaib jarak untuk operasi korona antara beberapa keluarga graf, seperti graf lengkap, graf siklus, graf lintasan, dan graf bintang.Kata Kunci: pelabelan ajaib jarak; operasi korona; graf lengkap; graf siklus; graf lintasan; graf bintang. 2020MSC: